2018
DOI: 10.1136/archdischild-2018-315676
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory sleep studies at home: experience in research and clinical cohorts

Abstract: ObjectiveTo evaluate the success rates of home cardiorespiratory polygraphy in children under investigation for sleep-disordered breathing and parent perspectives on equipment use at home.DesignProspective observational study.SettingSheffield, Evelina London and Southampton Children’s Hospitals.PatientsData are reported for 194 research participants with Down syndrome, aged 0.5–5.9 years across the three centres and 61 clinical patients aged 0.4–19.5 years from one centre, all of whom had home cardiorespirator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…OSA was assessed using the SOMNOtouch device (SOMNOmedics, Germany) comprising chest and abdominal respiratory inductance plethysmography (RIP) bands, internal pulse oximetry, nasal pressure flow with snore sensor, body position sensor, and actigraphy. We have previously reported our positive experience of domiciliary studies in this population (34). A sleep log recorded sleep onset, night waking's, and morning wake up times.…”
Section: Domiciliary Cardiorespiratory Polygraphymentioning
confidence: 99%
See 1 more Smart Citation
“…OSA was assessed using the SOMNOtouch device (SOMNOmedics, Germany) comprising chest and abdominal respiratory inductance plethysmography (RIP) bands, internal pulse oximetry, nasal pressure flow with snore sensor, body position sensor, and actigraphy. We have previously reported our positive experience of domiciliary studies in this population (34). A sleep log recorded sleep onset, night waking's, and morning wake up times.…”
Section: Domiciliary Cardiorespiratory Polygraphymentioning
confidence: 99%
“…36.16 (SD 20.6) (range 6-71)34.87 (SD 20.3) (range: 6-71) 38.68 (SD 21.1) (range 6-71) 0.659 BM1 > 95 th centile [restricted to those aged ≥ 2Further clarification of educational level: 1. GCSE at level C: has passed examinations conducted at the age of 16 years, 2.…”
mentioning
confidence: 99%
“…require surveillance for SDB, even in the absence of symptoms. Kingshott et al have recently shown a more encouraging outcome to cardiopulmonary polygraphy studies being performed at home in children, with 82% of clinical studies being successful at first attempt and parents confirming ease of use [ 25 ].…”
Section: National Documentsmentioning
confidence: 99%
“…PSG may also be valuable as it also allows recording of the mask pressure in order to monitor the delivered pressure, but also detects leaks and patient-ventilator synchrony (3), as well as identifying and characterizing residual respiratory events (26,27). Whether P(S)G should be done only during inhospital overnight or also at home (23) is not clear, because of the lack of studies reporting the use and feasibility of P(S)G at home in children receiving noninvasive respiratory support (28,29).…”
Section: Poly(somno)graphy (P(s)g)mentioning
confidence: 99%